Effect of mean droplet size distribution of emulsions on stability during storage / Qallishah Kamal Azman - Kamal Azman, Qallishah (2014)
The mean droplet size of an emulsion plays a major role in determining the stability of an emulsion. Stability of an emulsion preparation is important to prolong its shelf life. The objectives of this study were to investigate the influence of droplet size distribution on the stability of an emulsion and to assess and evaluate the stability of emulsion by using accelerated stability study. Four oil-in-water (0/W) emulsions with different mean droplet sizes were prepared. These four emulsions are then tested for their stability using the LUMiFuge based on gravitation simulation by using mechanical centrifugal system. The LUMiFuge machine was used in the accelerated stability study to speed up the processes of instabilities. Stability analysis was carried out, relating the mean droplet size distribution of the emulsion to its stability. The transmission profiles that were obtained from the LUMiFuge can be used to study the kinetics of the droplets leading the phase separation and becoming instable. Results demonstrated that emulsion with smaller mean droplet size does have better stability as compared to emulsions with larger mean droplet size.